Sejari Padlet (Semangat Belajar IPS Dengan Padlet) - Irwan Prabowo; Heri Maria Zulfiati (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
SEJARI PADLET (Semangat Belajar IPS dengan Padlet) which is carried out on grade 6 students at Karangasem State Elementary School aims to increase students' enthusiasm or interest in learning. Padlet application as a container for sharing learning materials from teachers. Students independently explore the features of the Padlet application which has been filled in with learning material by the teacher. Students do not need to download the application but simply open the link. The Padlet application can be opened at any time so students can study the material again in sequence. Best practice has been implemented by applying the learning by doing method in several stages. The first stage is the preparation stage, the second stage is training, the third stage is the implementation of the learning process. The results of questionnaire analysis and observations during social studies learning before and after using the Padlet application increased by 42.8% to 86.8% from 44% before learning using the Padlet application. Previously, only around 4 students out of 9 students showed interest in taking part in social studies lessons. After using the Padlet application, around 8 out of 9 students have shown interest in taking part in social studies learning. The average student learning outcomes also increased by 13.75 to 90 from the previous 76.25. All student learning outcomes are above or equal to the KKM, meaning students understand the lesson material more easily. From these data it can be concluded that the Padlet application is able to increase students' enthusiasm and interest in learning social studies.